The experiences of patients receiving haemodialysis treatment in an open setting environment at an academic hospital in Johannesburg - Khomba, Mayamiko Munthali (My University, 2014)
BACKGROUND: Patients receiving haemodialysis (HD) treatment experience a significant symptom burden and their needs are multifaceted. In HD unit, patients receive treatment in a diverse cultural and open ward setting. However, patients‟ experiences of receiving HD treatment in an open ward setting are not known. OBJECTIVES: The central aim of this study was to explore and describe the experiences of patients receiving HD treatment in an open setting environment at an academic hospital in Johannesburg. DESIGN: A qualitative, exploratory and descriptive study was conducted at a public, tertiary level academic hospital in Johannesburg after obtaining ethical approval from Wits University and relevant authorities. SETTING: The research setting for this study was an adult Chronic Renal Dialysis Unit. POPULATION: Sixteen adult (age 18 and above) patients receiving chronic HD treatment were recruited purposively in this study. INTERVENTIONS: An in-depth semi-structured interview was conducted either before or after receiving HD treatment, which was audio-recorded, transcribed then analysed by using Giorgi Phenomenological method. FINDINGS: A mood enhancer appeared a major theme as participants positively valued the open setting environment for their overall and psychological well-being. Participants expressed by being with others and sharing experiences, a sense of community likened to a family developed. Common to all participants‟ language was the use of the “we” in relation to being in the open setting environment. This expression of the “we” by participants was interpreted as a community concept. The use of “we” associated with the concept of community described as a space to which every patient receiving HD belonged. They described their experiences in a collective manner. This was evident in repetitive reference to their common space, being together, sharing experiences, and finding identity from one another, being understood and a sense of being protected with personal relations that extend beyond 10 years for some. This open space contributed to shaping their perception of body image and illness. The nurse‟s role in timeously providing HD care was appreciated by many. However, being exposed to multiple situations of chronic illness and treatment a sense of fear developed. Any negative event experienced, watched, observed, or heard in the HD unit triggered fear in the patients. Two common fears were of HD complications and the constant threat of death. Complications such as clotting, muscle cramps and collapsing because of hypotension as well as watching somebody dying on the machine were all reported in this study and so psychological counselling was felt to be very important. CONCLUSION The recommendations proposed in this study hopefully will assist HD staff to intervene and make adjustments to support patients‟ holistic needs. Further studies into patients receiving HD in open settings and mixed-gender space are required for diversity of experiences and knowledge from different settings. Keywords: Haemodialysis, hospital environment, open setting, patient experiences
Keywords: Hemodialysis; Kidney Failure, Chronic--treatment; Patient Acceptance of Health Care